Development of blood hemoglobin level early detection device based on a noninvasive optical platform. Issue 11 (November 2022) - Irzaman; Suryana, Yaya; Pambudi, Sabar; Widayanti, Tika; Jenie, Renan Prasta; Prastowo, Bayu; Har, Nazopatul Patonah; Rahmawaty, Vania; Dahrul, Muhammad; Aminullah; Kurniawan, Ade; Siskandar, Ridwan; et al.
Abstract: Blood hemoglobin levels are a reliable indicator for anemia screening, which generally uses an invasive system or takes blood using a syringe. Spectrophotometry can work by "substituting" the use of a phlebotomy tube needle with electromagnetic wave radiation or light. This study aims to develop and carry out a noninvasive diagnostic test for measuring hemoglobin levels. There are three main stages in this research: (i) measuring hemoglobin concentration and scanning an incident wavelength on standard hemoglobin solutions and blood controls, (ii) making a prototype variant of a noninvasive blood hemoglobin level measurement device, and (iii) testing the technology unit on the developed prototype. The measured hemoglobin value by the Trax Control Meter for low, middle, and high levels is almost the same as the expected range values, namely, 13.09, 16.8, and 17.81 g/dL, respectively. Three sets of device prototype variants were successfully developed: (i) the noninvasive blood hemoglobin level measuring device based on Raspberry Pi Prototype on Infant Finger and Thigh Probes, (ii) the level measuring prototype noninvasive hemoglobin in blood based on Internet of Things and WebServer, and (iii) the prototype of noninvasive blood hemoglobin level measuring device on in vitro probe with reflectance method. Testing the accuracy of the Biorad MeterTrax Trilevel using a multiformula regression calculation using the ZunZun server shows that the tool has an accuracy ranging from 0.12 to 0.30 g/dL. Abstract : Portable device; Hb measurement; Noninvasive; Blood characterization.